Comparative testing of disinfectant efficacy on planktonic bacteria and bacterial biofilms using a new assay based on kinetic analysis of metabolic activity - Günther, Frank; Scherrer, Martin; Kaiser, Stefan J.; De Rosa, Annalisa; Mutters, Nico T. (Journal of applied microbiology, 2017)
Aims The aim of our study was to develop a new reproducible method for disinfectant efficacy testing on bacterial biofilms and to evaluate the efficacy of different disinfectants against biofilms. Clinical multidrug-resistant strains were chosen as test isolates to ensure practical relevance. Methods and Results We compared the standard qualitative suspension assay for disinfectant testing, which does not take into account biofilm formation, to the new biofilm viability assay that uses kinetic analysis of metabolic activity in biofilms after disinfectant exposure to evaluate disinfectant efficacy. In addition, the efficacy of four standard disinfectants to clinical isolates was tested using both methods. All tested disinfectants were effective against test isolates when in planktonic state using the standard qualitative suspension assay, while disinfectants were only weakly effective against bacteria in biofilms. Conclusions Disinfectant efficacy testing on planktonic organisms ignores biofilms and overestimates disinfectant susceptibility of bacteria. However, biofilm forming, e.g. on medical devices or hospital surfaces, is the natural state of bacterial living and needs to be considered in disinfectant testing. Significance and Impact of the Study Although bacterial biofilms are the predominant manner of bacterial colonization, most standard procedures for antimicrobial susceptibility testing and efficacy testing of disinfectants are adapted for application to planktonic bacteria. To our knowledge, this is the first study to use a newly developed microplate-based biofilm test system that uses kinetic analysis of the metabolic activity in biofilms, after disinfectant exposure, to evaluate disinfectant efficacy. Our study shows that findings obtained from disinfectant efficacy testing on planktonic bacteria cannot be extrapolated to predict disinfectant efficacy on bacterial biofilms of clinically relevant multidrug-resistant organisms.